Σύνθεση νανοϋλικών με βάση το διοξείδιο του τιτανίου για φωτοκαταλυτικές εφαρμογές - Καρπεράκης, Χρήστος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2016)
Synthetic organic dyes comprise a significant part of industrial water effluents, as they are discharged in abundance by many manufacturing industries (e.g. textile industries). The potential carcinogenic properties of these dyes render their safe disposal a major environmental concern. The colored wastewater in the presence of the aforementioned dyes is a major cause of eutrophication and production of hazardous byproducts through processes such as oxidation, hydrolysis, or other chemical reactions taking place in the wastewater phase. The colored wastewater release in the ecosystem may also block both sunlight penetration and oxygen dissolution, which are essential for energy intake and the preservation of aquatic life. Thus there is a dire need to treat these colored effluents before discharging them into various water bodies. For the safe removal of dye pollutants, traditional physical techniques (adsorption on activated carbon, ultrafiltration, reverse osmosis, coagulation by chemical agents, ion exchange on synthetic adsorbent resins, etc.) can generally be used efficiently. Nevertheless, they are non-destructive for the pollutant, since they merely transfer the organic compounds from liquid to another phase, thus causing secondary pollution. Consequently, costly regeneration of adsorbent materials and post-treatment of solid-wastes, which are expensive operations, are mandated. Due to the large degree of aromatics present in dye molecules and the stability of modern dyes, conventional biological treatment methods (Cyclic Activated Sludge System) are ineffective for decolorization and degradation. Lately, Advanced Oxidation Processes (AOPs), such as photochemical processes, Fenton, photo-Fenton, Fenton-like, ozonation and photocatalysis, are being applied to treat dye effluents with encouraging results. AOPs were based on the generation of very reactive species such as hydroxyl radicals (•OH), that oxidize a broad range of pollutants quickly and non-selectively. Among AOPs, heterogeneous photocatalysis appears as the most promising pollutant destructive technology. Heterogeneous photocatalytic processes involve irradiation–usually UV-A (λ= 320 – 400 nm) or solar irradiation, in the presence of a semiconductor acting as a catalyst for the production of free hydroxyl radicals. The basic mechanism for generating •ΟΗ involves the adsorption of a photon, the generation of an electron-hole pair (e_cb^-+ h_vb^+) and subsequently the production of •ΟΗ. The photo-generation of a hole-electron pair is a reversible process and it can therefore correspondingly diminish the rate of •ΟΗ production. The generated electrons react with adsorbed oxygen and this inhibits the recombination step. In the absence of a surface e- acceptor species recombination of the hole-electron pair proceeds very fast. The photogenerated holes can oxidize the organic molecule to form R+, or react with OH− or H2O, thus oxidizing them into •OH radicals. Together with other highly oxidant species (peroxide radicals) they are reported in the literature to be responsible for the heterogeneous photodecomposition of organic substrates as dyes. Considering efficient photocatalysts, nanometric commercial Titania (Degussa P25), is one of the most promising materials due to its potent photocatalytic properties. However, it strongly suffers from a low photocatalytic activity when employed under visible light, while also exhibiting a positive correlation with the appearance of human lung cancer, attributed to the presence of respirable, nano-sized particles. To overcome these problems, new materials need to be produced and tested for their photocatalytic properties. Utilizing high energy ultrasounds (US), in order to modify the surface of a ceramic substrate with metallic nanoparticles, is considered an easy, fast and effective approach for synthesizing photocatalysts and increase their photocatalytic potential in the visible range. In the present thesis, a sonochemical procedure exploiting high energy ultrasounds was used in order to obtain decoration (10% W/W) of Ag metallic nanoparticles (NPs) on the surface of commercial micrometric Titania Kronos 1077 (100% anatase, average crystallite size: 110nm, Eg=3.2eV). To investigate the photocatalytic activity of the prepared sample the molecule of Methylene Blue dye was used. A parametric study of the photocatalytic oxidation was carried out, accounting for variable pH and amount of employed catalyst. Tests were conducted both under UV-A light and artificial visible light. To ensure the decoration of silver NPs on the titanium dioxide substrate two different solutions were prepared. The first solution (A) contains the silver precursor AgNO3 (Sigma Aldrich, 99.0%), PVP (polyvinylpyrrolidone, Sigma Aldrich, 99.0%), TiO2 Kronos 1077 and dist. H2O. The second solution (B) contains NaBH4 (Sigma Aldrich, 99.0%) and dist. H2O. First, solution A was treated by US generated using a VCX 750 by SONICS®, utilizing a 200W US generator and a sonication extension horn (US frequency: 20 kHz) of 13 mm diameter and maintaining the temperature at 30◦C using a heating circulator for 10 minutes with 33.0% amplitude and an intensity of 30Wcm−2. Without stopping sonication, solution B was then mixed with solution A and sonication continued for one hour. The presence of NaBH4 acts as a reducing agent on the silver precursor molecules while PVP, which acts as a surfactant, plays a crucial role on the morphology and size of the final product. Ultrasound is fundamental for both the formation of NPs from the precursor and for their optimal distribution on the TiO2 support surface. Indeed, ultrasonic irradiation speeds up the diffusion of solute in the reaction system, as well as influences the selective adsorption of the surfactant on silver, thus inducing elongation or compression in defined directions, affecting the particles morphology. Moreover, the use of US allows working in conditions that do not require high temperatures and thus they are not energy intensive. Finally, the sonicated mixture is centrifuged in order to remove the solvent and it is then washed with dist. water. After centrifugation, the obtained slurry mixture was put in an oven for two hours at 400 ◦C. XRD analysis of the modified sample showed that surface decoration does not affect the structural properties of Kronos 1077. The XRD pattern exhibits the peaks characteristic of the anatase phase [ICDD anatase file no. 21-1272]. The TEM analysis of bare Kronos 1077 shows that it is characterized by an average crystallites dimensions lying in the 100–150nm range. Respectively, the decorated sample exhibits the main morphological features typical of the parent Kronos system, with an average Ag nanoparticle size on the Kronos surface lying in the 10–30nm range. In order to test the photocalytic properties of the prepared sample, compared to the bare one, and examine certain parameters that effect the degradation of Methylene Blue molecule (pH, catalyst loading), a photocalytic apparatus was designed and build in the lab. The experiments were carried out in a glass vessel of 120ml, transparent to UV-A irradiation. A total of 6 lamps, 11W each, were placed above the vessel either for UV-A (PL-S 11W/10/2P 1CT, λmax=365nm) or for VL, (PL-S 11W/865/2P 1CT, λmax=545nm ) irradiation. Since dyes are colored in nature, it is straightforward to monitor their color change during the course of the experiment. In photocatalytic studies, the sample is typically exposed to UV or VL irradiation for a given time period and the changes in solution property (such as color) are observed by a spectrophotometer. To monitor the photodegradation of the dye a sample of the solution after irradiation is transferred to a cuvette and subjected to absorption studies on a UV-Vis spectrophotometer (U-5100 Hitachi). The degree of decoloration (τ) is then calculated from the decrease of absorbance of the dye solution at its maximum absorption wavelength as follows: τ=[1-A_i/A_0 ]×100 where, A0 and Ai are the absorbance values of the dye solution, before and after irradiation respectively. After each measurement the sample is returned back to the glass vessel. The MB removal was studied by monitoring the degradation of the MB dye in an aqueous solution (100ml, 2×10-5M), under continuous stirring and exposure to UV-A light irradiation or visible light (VL). The characteristic absorption at 663 nm was used to determine the MB concentration. In the experiments regarding the photodegradation efficiency of MB, as affected by the initial pH of the solution, the catalyst loading was kept constant at 2 mg and pH varied from the natural pH at 5.8 to 4 and 2. Respectively, the experiments regarding the catalyst loading, the pH of the suspension was fixed and kept constant at pH value 4 and the catalyst loading varied between 1, 2 and 3 mg.. Before starting each experiment the prepared suspension was put in an ultrasonic bath for 30 minutes under dark conditions to ensure the best possible distribution of the catalysts particles in the solution and a maximum absorption of the dye molecules onto the catalyst surface. A benchmark absorption spectrum, before irradiation, was obtained. Subsequently, the lamps were turned on and the experiments lasted for one hour of illumination, taking measurements of the absorption spectra at specific time intervals during the illumination process. The photocatalytic studies under different pH solutions showed that at lower pH values the photocatalytic oxidation is enhanced. The variation in solution pH changes the surface charge of TiO2 particles and shifts the potentials of the catalytic reactions taking place. The surface of Titania will remain positively charged in an acidic medium and negatively charged in an alkaline medium because of protonation or deprotonation respectively. Therefore as the pH value decreases, the reaction between the photogenarated h_vb^+ and the negative hydroxyl molecules OH− is predominant, due to electrostatic attractions, causing the formation of more hydroxyl radicals •OH resulting in a faster degradation rate for MB. Respectively, the increase of the catalyst loading in the solution improves the photooxidation of MB due to the increased number of active sites on the photocatalyst surface thus causing an increase in the number of •OH radicals, which can take part in the actual discoloration of the dye solution. A similar pattern but much lower degradation percentages were observed under VL irradiation. The above was anticipated due to the present low photons energy causing a reduced electron-hole pair generation and resulting in a decreased rate of formation for •OH radicals and eventually to a lower photocatalytic oxidation of MB. In every examined case, the decorated sample with Ag NPs exhibited better photocatalytic activity than the unmodified, bare Kronos 1077. Species like metals NPs on the catalyst surface are able to act as an electron trap, reducing the electron–hole recombination rate, and also increase the number of active sites on the surface of the catalyst, causing the formation of more •OH radicals, leading to higher oxidation rates. Summarizing the results, the decorated sample achieved to degrade almost 80% of the initial dye concentration, under pH value 2 (2mg catalyst) or with 3mg catalyst loading (pH=4) under one hour of UV-A irradiation, whereas bare Kronos 1077 degraded 73% and 67% respectively. Under VL irradiation, Kronos1077/Ag achieved a 34% degradation under pH value 2 (2mg catalyst) and a 24% using 3 mg catalyst loading (pH=4) while bare Kronos achieved almost 20% in both cases. Through the innovations introduced by sonochemistry, it was possible to obtain a novel process of surface decoration for a pigmentary micro-TiO2. This modification method was observed to improve the photocatalytic activity of the material, in particular under the visible light, where bare TiO2 was found to be a less effective photocatalyst. Significant differences in decolorization and degradation rates were found depending on system parameters. With proper combinations of TiO2 loading and initial pH, decolorization and degradation efficiencies can reach a maximum potential.